An Effect of Principal’s Leadership Style and Work Motivation Toward Teacher’s Performance - Santoso, Adi; Fitria, Happy; Mulyadi, Mulyadi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to determine and describe the influence of the principal’s leadership style and work motivation on the performance of teachers at SMKN 1 Lempuing, Ogan Komering Ilir Regency, partially and simultaneously. This research method is quantitative correlational, with the research population being all teachers at SMKN 1 Lempuing, totaling 52 teachers, all of whom were then used as the research sample. Data was collected by documentation and questionnaires. Analyzed with descriptive statistics and analytical hypotheses using simple regression and multiple regression with the help of SPSS 25. The results of this study show that there is a significant influence of the principal’s leadership style and work motivation on teacher’s performance partially and simultaneously. It means the education stakeholders need to have good principal’s leadership style and work motivation to get good teacher’s performance.